STATISTICAL ANALYSIS OF WIND SPEED DISTRI BUTION WITH SINOP TURKEY APPLICATION - Balpetek, N.; Akpınar, Ebru (My University, 2019)
In this study, the wind energy potential of the Sinop region was analyzed statistically by using the TurkishState Meteorological Station’s hourly wind speed data between the years of 2005 2014. The two parameter Weibulland one parameter Rayleigh probabi lity distribution functions were used to determine the wind energy potential ofthe region. The probability distribution functions were derived from the cumulative function and used to calculate themean wind speed and the variance of the actual data. The best way of representing the performance of the Weibulland Rayleigh distributions is to use the statistical parameters such as the correlation coefficient (R 2 ), chi square (? 2 )and the root mean square error analysis (RMSE). The results of the study show ed that Sinop has a mean wind speedof 3.36 m/s with a maximum value of 4.28 m/s in February of 2011, and a minimum value of 2.41 m/s in March of2013, while the corresponding mean wind power density is approximately 33.31 W/m 2 for the whole year. In gener al,it was determined the wind speed is higher during some winter and spring months, notably February and March, andis lower during the autumn months. The Weibull distribution function was found to be more appropriate than theRayleigh distribution functi on.
Keywords: Fizik; Uygulamalı; İstatistik ve Olasılık